IMPLEMENTASI E-GOVERNMENT DI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN TEMANGGUNG - Nur Isnaeni, Latifah; Nurcahyanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
This research is based on the low SPBE (Electronic-Based Government System) index of Temanggung Regency, which is 2.80, compared to other regions in Central Java Province, despite being supported by the Regent Regulation of Temanggung No. 83 of 2021 regarding the Implementation Guidelines for Regional Regulation of Temanggung Regency No. 22 of 2020 on the Implementation of Electronic-Based Government Systems. The purpose of this study is to analyze the implementation of e-government based on the principles of effectiveness, integration, sustainability, efficiency, accountability, transparency, interoperability, and security, as well as the factors influencing the implementation, such as communication, resources, disposition, and bureaucratic structure at the Department of Communication and Information of Temanggung Regency. The research method used is descriptive qualitative. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study show that the implementation of e-government at the Department of Communication and Information of Temanggung Regency has been well executed in terms of integration, efficiency, and transparency. However, improvements are still needed in the aspects of effectiveness, sustainability, accountability, interoperability, and security. On the other hand, challenges related to resources and disposition have been identified as factors affecting the implementation of e-government at the Department of Communication and Information of Temanggung Regency.